Cinema Encruzilhada and SECNEB Filmography: performances and black cultures in the documentary - Gama, Alessandra Regina (2024)
In this article, we address the representation of Afro-Brazilian cosmogony in documentaries, considering aesthetic and political aspects of the relationship between cinema and the terreiros. Our objective is to reflect on the issues of representation of Afro-diasporic cultures in the documentary field, intertwined with the theoretical field of cultural performances, in the formation of a crossroads aesthetic. Starting from the idea of ​​cinema as a point of intersection, as crossroads cinema, we analyze the documentary trilogy produced by the Society for the Study of Black Culture in Brazil — SECNEB, in the late 80s, composed of the films Orixá Ninu Ilê (Dir. Juana Elbein dos Santos, 1978), Iyá-Mi-Agbá (Dir. Juana Elbein dos Santos 1981) and Egungun (Dir. Carlos Brajsblat, 1982). The trilogy explores the disputes surrounding the ways of representing ancestral knowledge, reflecting, in the works, the clash between cinema and cultural decolonization, from the point of view of the relationships between body and performance, in the articulation of knowledge.